2006
DOI: 10.1038/sj.ejhg.5201623
|View full text |Cite
|
Sign up to set email alerts
|

Genistein-mediated inhibition of glycosaminoglycan synthesis as a basis for gene expression-targeted isoflavone therapy for mucopolysaccharidoses

Abstract: Mucopolysaccharidoses (MPS) are inherited, severe, progressive, metabolic disorders caused by deficiencies in different enzymes involved in degradation of glycosaminoglycans (GAGs). Although enzyme replacement therapy (ERT) has recently been available for MPS type I, and clinical trials have been performed in ERT for MPS II and MPS VI, there is little chance that this kind of treatment may be effective for neurodegenerative forms of MPS (due to inefficient delivery of enzymes to central nervous system through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
191
1
8

Year Published

2007
2007
2013
2013

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 168 publications
(210 citation statements)
references
References 35 publications
10
191
1
8
Order By: Relevance
“…Genistein at concentrations between 10 and 30 lM inhibited GAG synthesis and reduced lysosomal GAG storage (Piotrowska et al 2006). Some other flavonoids were also able to decrease GAG storage in MPS IIIA, IIIB, and VII cells (Arfi et al 2010;Piotrowska et al 2010;Kloska et al 2011).…”
Section: Efficacy Of Srt In In Vitro Studies Experiments With Animalmentioning
confidence: 94%
See 1 more Smart Citation
“…Genistein at concentrations between 10 and 30 lM inhibited GAG synthesis and reduced lysosomal GAG storage (Piotrowska et al 2006). Some other flavonoids were also able to decrease GAG storage in MPS IIIA, IIIB, and VII cells (Arfi et al 2010;Piotrowska et al 2010;Kloska et al 2011).…”
Section: Efficacy Of Srt In In Vitro Studies Experiments With Animalmentioning
confidence: 94%
“…Genistein (5, 7-dihydroxy-3-[4-hydroxyphenyl]-4H-1-benzopyran-4-one), a natural isoflavone occurring in many plants, significantly inhibited GAG synthesis when added to cultures of fibroblasts of MPS I, MPS II, MPS IIIA and MPS IIIB patients (Piotrowska et al 2006). In contrary to rhodamine B, whose detailed mechanism of action remains unknown, it was possible to learn about the way by which genistein slows the GAG synthesis down.…”
Section: Substrate Reduction Therapies (Srps) For Mpsmentioning
confidence: 99%
“…If the expression studies confirm this hypothesis, active site-specific inhibitors of the enzyme could be tested for their ability to stabilize the mutants and modify their conformation closer to that of the wild-type enzyme, increasing the level of their residual activity as has been demonstrated for other lysosomal enzymes (reviewed in Fan [2003]; Desnick [2004]). Together with the inhibitors of heparan sulfate synthesis [Piotrowska et al, 2006;Jakó bkiewicz-Banecka et al, 2007], such ''pharmacological chaperones'' may be an interesting subject of future research in this area.…”
Section: Clinical and Diagnostic Relevancementioning
confidence: 99%
“…3,4 Moreover, treatment of MPS IIIA mice with rhodamine B resulted in a behavioral improvement, 5 and pilot clinical studies with the use of a genisteinrich extract for treatment of MPS IIIA and MPS IIIB human patients showed statistically significant improvement is all tested parameters, including cognitive functions. 6 The improvement in the CNS functions in both mice and humans treated with inhibitors of GAG synthesis (either rhodamine B or genistein) were proposed to be due to a possibility of crossing the blood-brain barrier by these small molecules, and indicated that impairment of substrate production may be an effective therapeutic option for patients suffering from neuronopathic forms of lysosomal storage diseases.…”
Section: Introductionmentioning
confidence: 97%